ANALYSIS OF THE CORONA CRISIS’ IMPACT ON THE ECONOMY OF UKRAINE - Shevchuk , Tetyana; Sidelnуk, Elena; Kravchuk, Halyna (Socio-economic relations in the digital society, 2021)
The article explores the essence and nature of the economic crisis caused by the COVID-19 pandemic, which in combination with the coronavirus network infodemia caused the community to plunge into a deep systemic crisis. Society has faced global challenges, which need to be addressed through a series of well-considered measures, primarily state support for small and medium-sized businesses, stimulating job growth, improving the investment climate and attracting investment.The uniqueness and features of the coronary crisis are emphasized. After all, the COVID-19 pandemic is the first experience in recent history when a purely biological factor has acquired a virtually independent life in the social sphere and has shown superpower in influencing the political, legal, socio-economic spheres, interstate relations and community life, dictating behavior national communities, in which the imperatives of health and life clearly prevail over previously inviolable values. The assessments made by scientists-analysts concerning the forecasts of the coronary crisis and the factors that pose a threat to the world economy are considered. Ukraine found itself in a new system of risks associated with the global economic recession, which prompted a slowdown in economic dynamics.The authors analyze the impact of the introduction of strict quarantine conditions on various areas of economic activity in Ukraine. The decline in business activity provoked by the pandemic, the deteriorating situation in world markets for a number of manufactured goods, the weakening of investment activity, etc. has led to a decline in all sectors of the economy. Analysis of real GDP showed that in 2020 the economy returned to 2012. Accordingly, the performance indicators of the state budget of Ukraine have significantly decreased. The country’s banking system is also in a difficult situation. However, the situation in the money market remains stable and the banking system has a fairly high level of liquidity. Banks have sufficient resources for uninterrupted operation, even in a deteriorating mood of the population and business under the influence of negative news from world markets. For the first time in history during the crisis, banking institutions did not become a factor in increasing economic instability.
Keywords: economy; economic crisis; corona crisis; pandemic; economic indicators